Internationalization of Education in the Post-Pandemic: A Model for Sustainable Education - Leoncio Peralta Olobia (East Asian Journal of Multidisciplinary Research, 2023)
As society slowly transitions to the post-pandemic, internationalization as a form of educational resilience is exemplified through uptake in knowledge, skills, research, and multicultural understanding while fostering bigger and more profound relationships with global communities in the spirit of interconnectedness and international recognition. This paper argues that internationalization is a process with two sides of the same coin. On the one hand, localization of internationalized learning rallies for identity expressions that are relevant to people’s needs which can easily be eradicated through repeated encroachment upon indigenous and vulnerable sensibilities. On the other hand, a locally adopted education extends its influential arms to international borders giving rise to a model of sustainable education in post-pandemic society where hybridity, inclusivity, decolonization, and blended education are relevant and emancipatory themes embraced through localization of international, and internationalization of localized education.